2019
DOI: 10.2174/1874149501913010172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rebar on Ductility of Moment-resisting Frame with Concrete-filled Tube Column

Abstract: Background: Today, many developed countries use the Concrete-Filled Steel tube columns (CFT) to construct high-rise building and bridge piers. Objective: This paper investigates the effect of rebar inside the concrete core of CFT columns. Materials and Methods: For this purpose, the structural performance of three two-span frames is evaluated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In order to improve the poor fire resistance and corrosion resistance of concrete-filled steel tubes and solve the issue of the degradation rate of the mechanical properties of components being too fast, scholars studied reinforced-concrete-filled steel tube composite components [34][35][36][37][38]. It was found that, after the reinforcement was configured in traditional concrete-filled steel tube components, the steel skeleton arranged by longitudinal reinforcement and stirrup formed a double constraint on the core concrete to improve the mechanical properties of the components as well as the fire resistance and corrosion resistance of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the poor fire resistance and corrosion resistance of concrete-filled steel tubes and solve the issue of the degradation rate of the mechanical properties of components being too fast, scholars studied reinforced-concrete-filled steel tube composite components [34][35][36][37][38]. It was found that, after the reinforcement was configured in traditional concrete-filled steel tube components, the steel skeleton arranged by longitudinal reinforcement and stirrup formed a double constraint on the core concrete to improve the mechanical properties of the components as well as the fire resistance and corrosion resistance of the structure.…”
Section: Introductionmentioning
confidence: 99%